1986
DOI: 10.1111/j.1600-0765.1986.tb01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cementum‐like tissue in vitro by cells cultured from bone: a light and electron microscope study

Abstract: Cells obtained from calvariae of fetal rats, human gingival connective tissue and periodontal ligament of rat molars were each co‐cultured in vitro with non‐demineralized and partly demineralized root slices in nutrient medium containing 50 μGg/ml ascorbic acid and 10 mM B‐glyeerophosphate, in order to determine whether the root slices could affect the phenotype expressed by the cells. The cultures were examined by light and transmission electron microscopy. Nodules of bone‐like tissue, resembling those previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 24 publications
3
49
0
2
Order By: Relevance
“…The thesis that cementoblasts and osteoblasts in the periodontium commonly originate from precursor cells residing in the alveolar bone is also supported by previous observations (Gould et al, 1977;Melcher et al, 1986). Our data are also consistent with the data reported by Rajishankar and colleagues (Rajishankar et al, 1998).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The thesis that cementoblasts and osteoblasts in the periodontium commonly originate from precursor cells residing in the alveolar bone is also supported by previous observations (Gould et al, 1977;Melcher et al, 1986). Our data are also consistent with the data reported by Rajishankar and colleagues (Rajishankar et al, 1998).…”
Section: Discussionsupporting
confidence: 83%
“…Since fibroblasts are predominant in the PDL (Berkovitz and Shore, 1995;Beertsen et al, 1997) and are capable of producing and digesting matrix components, fibroblastic cells have been assumed to be responsible for self-renewal of the PDL and regeneration of periodontal tissue. Indeed, experiments dealing with periodontal wound healing have suggested that PDL fibroblast populations may play an integral role in PDL regeneration (Melcher et al, 1986;McCulloch et al, 1987;Magnusson et al, 1990;Beertsen et al, 1997). Since these experiments were carried out with mixed cell populations of PDL tissues and/or cells of endosteal spaces, however, it is difficult to determine the cellular phenotypes that are required for regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…At least one study has shown that in vitro only cells derived from embryonic rat calvaria have the capacity to form a cementum-like material. 29 There are no studies demonstrating the ability of gingival cells, either in vivo or in vitro, to form periodontal tissues such as cementum and bone. Although attempts have been made, 30 the results are inconclusive on the ability of cells derived from gingiva.…”
Section: Cells Of the Periodontiummentioning
confidence: 99%
“…Cementoid matrix and oriented bundles of collagen fibrils (presumably ligament fibers) are seen deposited over the electron-dense layer during cementum regeneration ( Figures 3B and 4). 13 In their study on the formation of cementum-like tissue by bone cells cultured from calvaria of rats, Melcher et al 29 also describe "osmiophilic incremental lines" between the curetted roots and the new matrix. This osmiophilic structure resembles the electrondense layer described by others.…”
Section: Behavior Of Cells In the Periodontal Tissues -In Vivo Andmentioning
confidence: 99%
“…31 The similar staining patterns of osteoblasts and cementoblasts in cellular cementum indicate that they are phenotypically similar and may be derived from a common osteoprogenitor cell. [32][33][34] Therefore, it has been hypothesized that reparative cementum is derived from osteoblasts.…”
Section: Discussionmentioning
confidence: 99%